Study of structural surface modified tin oxide membrane prepared by sol-gel route sintered at 400 degrees C - Santos, LRB; Belin, S.; Briois, V; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Larbot, A. (Kluwer Academic Publ, 2003)
This work describes the chemical modification by Tiron(R) molecules of the surface of SnO2 nanoparticles used to prepare nanoporous membranes. Samples prepared with Tiron(R) content between 1 and 20 wt% and fired at 400 C were characterised by X-Ray Powder Diffraction (XRPD), Extended X-ray Absorption Fine Structure (EXAFS), N-2 adsorption isotherms analysis and permeation experiments. XRPD and EXAFS results show a continuous reduction of crystallite size by increasing the Tiron(R) contents until 7.5 wt%. The control exercised by Tiron(R) modifying agent in crystallite growth allows the fine tuning of the average pore size that can be screened from 0.4 to 4 nm as the amount of grafted molecules decreases from 10 to 0 wt%. In consequence, the membrane cut-off can be screened from 1500 to 3500 g.mol(-1).
Keywords: ceramic membranes; surface modification; ultrafiltration; porosity